2013
DOI: 10.1007/s12072-013-9456-x
|View full text |Cite
|
Sign up to set email alerts
|

Management of acute kidney injury in cirrhosis

Abstract: Acute kidney injury (AKI) is a relatively frequent problem, occurring in approximately 20 % of hospitalized patients with cirrhosis. Although serum creatinine (S Cr) is the most commonly used method to determine AKI because of easy availability and low cost, practically it underestimates the extent of kidney injury in patients with chronic liver disease. AKI is defined as an abrupt rise in S Cr of 0.3 mg/dl or more (>26.4 mmol/l) or an increase of 150 % or more (1.5-fold) from baseline. The cause of AKI in cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
6
0
4
Order By: Relevance
“…The predominant causes of AKI in cirrhosis can be either functional or structural. Functional causes include pre-renal azotemia and hepatorenal syndrome (HRS), while structural causes are predominantly due to intrinsic renal disease which may be tubulo-interstitial or glomerular in origin [26]. The importance of etiopathological diagnosis was demonstrated by Martín-Llahí et al, who found that the most common causes of AKI in cirrhosis were pre-renal azotemia, acute tubular necrosis (ATN) and HRS [27].…”
Section: Classification Of Kidney Injury In Liver Failurementioning
confidence: 99%
See 2 more Smart Citations
“…The predominant causes of AKI in cirrhosis can be either functional or structural. Functional causes include pre-renal azotemia and hepatorenal syndrome (HRS), while structural causes are predominantly due to intrinsic renal disease which may be tubulo-interstitial or glomerular in origin [26]. The importance of etiopathological diagnosis was demonstrated by Martín-Llahí et al, who found that the most common causes of AKI in cirrhosis were pre-renal azotemia, acute tubular necrosis (ATN) and HRS [27].…”
Section: Classification Of Kidney Injury In Liver Failurementioning
confidence: 99%
“…Injury to hepatocytes is known to produce DAMP (damage-associated molecular pattern) molecules, such as high-mobility group box-1 (HMGB1) proteins, which further increase the inflammatory response [13, 26]…”
Section: Pathophysiology Of Aki In Hrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hastanede takip edilen siroz hastalarının yaklaşık %20' sinde AKI gelişmektedir (6 (10). AKI gelişen 83 sirozlu hastanın değerlendirildiği bir çalışmada %53 ATN, %6 prerenal böbrek hasarı ve %22 HRS tespit edilmiştir (11).…”
Section: Etiyolojiunclassified
“…Оба состояния характеризуются снижением почечного кровотока и могут привести к развитию почечной недостаточности. Отдельно выделяют гипонатриемию, в основе которой лежит задержка жидкости, непропорциональная задержке натрия, из-за чего снижается его относительная концентрация в крови -гиперволемическая гипонатриемия [9,12].…”
Section: №2 (83) 2014unclassified